Learning, Indigenizing, and Delivering Forum Theatre Activities in Indigenous Communities: Reflections of Community Facilitators - Lines, Laurie-Ann; Anderson, Shaun; Jardine, Cindy; Marty, Casadaya (First Peoples Child & Family Review, 2024)
In many Indigenous communities, wellness is a holistic balance of spiritual, physical, mental, and emotional wellbeing through connections with self, family, community, and environment. Interventions to promote mental wellness (as a means of suicide prevention) with Indigenous youth thus need to focus on strengths and promoting these relations. First Nations and Métis communities in Alberta and the Northwest Territories in Canada partnered with academic researchers to adapt Forum Theatre as a mental health intervention for Indigenous youth. Forum Theatre, developed by Brazilian activist Augusto Boal, is based on playing games that encourage laughter, trust, and cooperation to build a community. The games lead to creating images with participants' bodies to reflect different life events, which are developed into a play with conflict and oppression. Through interaction with the play, community members explore solutions to the conflict.Indigenous community partners handpicked community members to train in facilitating Forum Theatre activities to deliver this mental health intervention. Our video showcases the reflections of a group of community facilitators and researchers on the process of being trained in Forum Theatre and indigenizing it for delivery to the participating communities. Community facilitators explain how they came to understand the potential and power of Forum Theatre activities. They describe their training experiences and briefly explain how they indigenized Forum Theatre in a manner that prioritized each community's assets and needs. Their description of the impact they saw in themselves, participants, and communities emphasizes the transformative nature of delivering indigenized Forum Theatre in communities.